Pemantauan dan Edukasi Sanitasi Kualitas air Sumur Bor pada Masyarakat di Dusun Paramppunganta Desa Kampili Kab Gowa - Alfina Baharuddin; Muhammad khidri Alwi; indasari indasari; Saskia Anrah Maharani; Adira Artika Aulia; Nurul Fadliah Mubakkira (Window of Community Dedication Journal, 2024)
Poor environmental sanitation factors include inadequate access to clean water, contributing to an increase in infectious diseases such as diarrhea.This research is descriptive quantitative The population in this study were 5 boreholes The population in this study was the community in Paramppungata Hamlet, Kampili Village, Gowa Regency of 200 people. The sampling technique with exhautif sampling method (total sampling) is that all populations are sampled in this study as many as 200 people. The results showed that the quality of borehole water in terms of physical parameters in the turbidity parameter exceeded the lowest NAB at point 3 (0.48), and the highest at point 5 was 240. Likewise with odor and taste parameters that are problematic at points 2, 3 and point 4. Chemical parameters meet the requirements of drinking water quality standards for both Fe, nitrate (No3) parameters, only the total hardness parameter does not meet the requirements. biological parameters at all points do not meet the drinking water quality requirements, the highest at point 3 by 5400 ml / l and the lowest at points 1 and 2 each by 130 ml